(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper we present the concepts and methods developed for the activities in communication systems for car-to-car communication to avoid Vehicle crash. From such communication systems, Controller area network (CAN) is a computer network protocol and bus standard designed to allow microcontrollers and devices to communicate with each other without a host computer. Modern automobiles are no longer mere mechanical devices; they are pervasively monitored and controlled by dozens of digital computers coordinated via internal vehicular networks. From a network-based systems the controller area network (CAN) to evaluate the feasibility of using such an in modern cars for a cooperative driving. The CAN module and multiple sensors have added in system for the passengers and vehicle safety. The cooperative and safe driving can be achieved by drivers by analysing another close vehicles data by drivers of car on their Dashboard.